Numerical Analysis and Experiments of Butt Welding Deformations for Panel Block Assembly - Hyunsu Ryu; Sungwook Kang; Kwangkook Lee (Applied Sciences, 2020)
In a shipyard, large numbers of temporary pieces are used to align welding lines of a block joint and prevent welding deformations in the block assembly stage. The use of many temporary pieces requires a great number of working man-hours, causing low productivity. In this study, experiments and numerical analyses of welding deformations were carried out in order to optimize the number of temporary pieces used. The quantitative relationship between the welding deformations and the temporary piece setting was established experimentally. In order to predict welding deformations considering temporary piece setting, a numerical method was proposed. The simulation results were verified through experiments. The optimal number of twenty-one temporary pieces needed to increase the productivity was calculated with the proposed numerical analysis method. Moreover, the proposed numerical analysis method could be used to establish guidelines and plans for a proper use of temporary pieces on the panel block assembly stage.